Identification of Navβ1 residues involved in the modulation of the sodium channel Nav1.4. - Angel A Islas (Public Library of Science (PLoS), 2013)
Voltage-gated sodium channels (VGSCs) are heteromeric protein complexes that initiate action potentials in excitable cells. The voltage-gated sodium channel accessory subunit, Navβ1, allosterically modulates the α subunit pore structure upon binding. To date, the molecular determinants of the interface remain unknown. We made use of sequence, knowledge and structure-based methods to identify residues critical to the association of the α and β1 Nav1.4 subunits. The Navβ1 point mutant C43A disrupted the modulation of voltage dependence of activation and inactivation and delayed the peak current decay, the recovery from inactivation, and induced a use-dependent decay upon depolarisation at 1 Hz. The Navβ1 mutant R89A selectively delayed channel inactivation and recovery from inactivation and had no effect on voltage dependence or repetitive depolarisations. Navβ1 mutants Y32A and G33M selectively modified the half voltage of inactivation without altering the kinetics. Despite low sequence identity, highly conserved structural elements were identified. Our models were consistent with published data and may help relate pathologies associated with VGSCs to the Navβ1 subunit.